Igreja Universal do Reino de Deus: análise de um caso de sucesso de estratégia por diferenciação - Resende, Paulo José Pereira de (2006)
Is it possible to see elements of an organizational strategy in churches practices, as we can do in public and private organizations? This work intend to show a case study about the Universal Church of the Kingdom of God, and study some factors that can be evidences of a strategic profile. It discusses the success that this church try to show: can it be proved? The conclusion of this study answer these questions.